Brand Authenticity: A 21-year bibliometric review and future outlook - Xiaoqing Li; Ming-Fook Lim; Aizah Nadia Aknie Ramlee; Brahim Chekima (SAGE Publications, 2024)
Brand Authenticity plays a crucial role in marketing activities. Over the past two decades, considerable progress has been made in the academic research on Brand Authenticity. However, a more comprehensive investigation on this subject still needs to be done. This paper aims to conduct a literature review using a bibliometric approach to summarize articles published between 2003 and 2023. The aim is to identify the publication trends, key authors, pivotal literature, significant journals, research clusters, intellectual base, and topic trends. We intend to establish a foundation for future agendas by consolidating existing achievements and identifying gaps. We employed two analysis tools, VOSviewer and Bibliometrix, to analyze and visualize 880 selected articles. The result indicates an overall increasing trend in publications; several authoritative scholars have emerged, and international collaborations are extensive. Several knowledge groups have also been formed, focusing on tourism, food and retail, and marketing/management. There need to be more significant breakthroughs, prompting the exploration of new topics to expand the scope of brand authenticity research. Some potential areas of investigation include exploring more antecedents and consequences variables, cross-cultural marketing, specific product authenticity, and the impact of corporate social responsibility on perceived authenticity. By addressing these directions, we can advance the understanding of brand authenticity and enrich the existing knowledge on this topic, thereby contributing to its future development.